Ancillary Studies in Evaluating Pediatric Brain Death - Henderson, Natalie; McDonald, Mark J. (Journal of Pediatric Intensive Care, 2017)
When confounding variables exist that inhibit the ability to diagnose brain death clinically in pediatric patients, ancillary tests may provide additional information for the practitioner in evaluating for the presence or absence of brain death. Multiple options exist but differ in availability, ease of administration, cost, safety profile, and reliability to accurately diagnose brain death. An important desirable quality of an ancillary test is eliminating false positives, which imply brain death when brain death is in fact not present. More commonly available ancillary studies include electroencephalograms, brain angiography through various modalities, brain stem auditory evoked potentials, and transcranial Doppler ultrasound. At this time, there is not an ancillary test with 100% reliability in diagnosing brain death that can replace the clinical brain death exam. Therefore, practitioners need to understand the strengths and limitations of the ancillary studies available at their hospital.
Keywords: pediatric; brain death; ancillary